Islamic Feminism and State Feminism: Competing Gender Discourses in Pakistan's Legal Reforms (2006–2023): Feminisme Islam dan Feminisme Negara: Diskursus Gender yang Bersaing dalam Reformasi Hukum di Pakistan (2006–2023) - Sabir, Muhammad Rehan; Dewi Candraningrum; Alwy Ahmed Mohamed (SiRad: Pelita Wawasan, 2026)
This study examines the role of Islamic feminist and state feminist discourses in Pakistan’s gender law reforms between 2006 and 2023. It is based on close reading of statutory texts and critical engagement with secondary scholarship on legislative processes. The analysis identifies distinct ways in which reform was justified in legal and policy debates. Islamic feminist discourse relied on Quranic reinterpretation to legitimate women’s rights within religious frameworks. State feminist discourse emphasized state protection, governance responsibilities, and international norms. Across cases, the two frameworks converged around shared policy objectives but diverged in their epistemological foundations. Debates over the Protection of Women (Criminal Law Amendment) Act 2006 reflected both religious and institutional rationales. Domestic violence legislation exposed tensions between family preservation and individual rights. The findings suggest that legal change in Pakistan requires navigating multiple sources of authority. Neither discourse alone was sufficient to secure reform. The study contributes to the scholarship on gender law reform in Muslim-majority contexts by showing how competing discourses both enable and limit legislative outcomes. [Penelitian ini mengkaji peran diskursus feminisme Islam dan feminisme negara dalam reformasi hukum gender di Pakistan antara tahun 2006 hingga 2023. Studi ini didasarkan pada pembacaan mendalam terhadap teks-teks peraturan perundang-undangan serta keterlibatan kritis dengan kajian sekunder mengenai proses legislasi. Analisis mengidentifikasi berbagai cara berbeda dalam pembenaran reformasi yang muncul dalam perdebatan hukum dan kebijakan. Diskursus feminisme Islam bertumpu pada penafsiran ulang Al-Qur’an untuk melegitimasi hak-hak perempuan dalam kerangka keagamaan. Sementara itu, diskursus feminisme negara menekankan perlindungan oleh negara, tanggung jawab tata kelola pemerintahan, serta norma-norma internasional. Dalam berbagai kasus, kedua kerangka tersebut bertemu pada tujuan kebijakan yang sama, namun berbeda dalam landasan epistemologisnya. Perdebatan mengenai Protection of Women (Criminal Law Amendment) Act tahun 2006 mencerminkan baik rasionalitas keagamaan maupun institusional. Legislasi tentang kekerasan dalam rumah tangga menyingkap ketegangan antara upaya pelestarian keluarga dan perlindungan hak individu. Temuan penelitian ini menunjukkan bahwa perubahan hukum di Pakistan menuntut kemampuan menavigasi berbagai sumber otoritas. Tidak satu pun dari kedua diskursus tersebut, secara berdiri sendiri, cukup untuk menjamin terwujudnya reformasi. Studi ini berkontribusi pada kajian reformasi hukum gender di konteks negara mayoritas Muslim dengan menunjukkan bagaimana diskursus yang saling bersaing sekaligus dapat memungkinkan dan membatasi hasil legislasi.]